Mood System in the Tourism Brochure of “Friendly Lombok” - Edfan Juliansyah; Sutiono Mahdi (Muhammadiyah University of Mataram, 2020)
Mood system can be found in every clause. This research was conducted to investigate the types of mood and their speech functions in the tourism brochure of “Friendly Lombok”. Qualitative descriptive research design was employed in conducting this research. The findings show that the mood system found in the tourism brochure of “Friendly Lombok” are declarative mood, interrogative mood, and imperative mood. In the brochure, the information and encouragement given by the author is delivered to the readers through the declarative mood. The interrogative mood functions to demand questions and attract the readers’ attention. The author’s authority to command and persuade the readers to take an action are expressed through the imperative mood. Based on the analysis, the declarative mood is the most common mood in the tourism brochure of “Friendly Lombok”. It shows that the author of the brochure tends to state information and encouragement of tourism aspects in Lombok to the readers.